An Experimental Performance Evaluation of the Wireless Network for Mobile Users - Ipatovs, A.; Petersons, E. (Elektronika ir Elektrotechnika, 2009)
The main idea is the detection of throughput in network with protocol 802.11.g. and WDS technology on different speeds of mobile user. Wireless network for mobile users was developed and described. Experimental performance measurements of the network were made. New method of evaluation of such wireless network was described. Ill. 5, bibl. 2 (In English; summaries in English, Russian and Lithuanian).